SAS Method Improves Early Reading Skills in Second Grade Students: Metode SAS Meningkatkan Kemampuan Membaca Awal pada Siswa Kelas Dua - Diffani Laila Sabila; Kemil Wachidah (Academia Open, 2025)
General Background: Early reading skills constitute a fundamental foundation for elementary school learning and are essential for academic development. Specific Background: Many lower-grade students still encounter difficulties in mastering beginning reading, necessitating structured instructional approaches such as the Structural Analytical Synthesis (SAS) method. Knowledge Gap: Despite prior studies on early reading instruction, limited evidence exists regarding the application of the SAS method to second-grade students within the specific context of SDN Lemah Putro 3. Aims: This study aimed to determine whether the SAS method could improve the initial reading ability of second-grade students at SDN Lemah Putro 3. Results: Using a pre-experimental one-group pretest–posttest design with 16 students, data collected through reading tests and observations showed a rise in mean scores from 80.4 on the pretest to 92.5 on the posttest, with paired sample t-test results indicating a statistically significant difference. Novelty: The study provides contextual empirical evidence on the application of the SAS method for early reading instruction at the second-grade level in an Indonesian elementary school setting. Implications: These findings suggest that the SAS method can serve as an alternative instructional strategy for beginning reading in primary education and support teachers in facilitating foundational literacy development. Highlights: Mean test scores increased from 80.4 before treatment to 92.5 after instruction. Statistical testing confirmed a significant difference between initial and final measurements. Learners showed greater fluency, accuracy, and pronunciation during reading tasks. Keywords: SAS Method; Early Reading Skills; Structural Analytical Synthesis; Elementary Students; Pre-Experimental Design